The DIVIDEND POLICY AND PROFITABILITY ON COMPANY VALUE WITH DEBT POLICY AS INTERVENING VARIABLES - Wiki Indah Larasati; Ana Susi Mulyani (PT Larva Wijaya Penerbit, 2022)
This research was conducted to find out the Effect of Dividend Policy and Profitability on Firm Value with Debt Policy as an Intervening Variable Case Study in automotive sub-sector companies listed on the Indonesia Stock Exchange for the 2010-2020 period. The variables in this study are Dividend Policy which is proxied by Dividend Payout Ratio (DPR), Profitability is proxied by Return On Assets (ROA), Firm Value is proxied by Price to Book Value (PBV), and Debt Policy is proxied by Debt Equity Ratio (DER). The object of research uses research variables. The data collection method is in the form of documentation of financial statements on the BEI through ICMD. The number of samples in this study were 5 companies which were determined using the purposive sampling method. The data analysis techniques in this study are descriptive and causal, classical assumption test, multiple linear regression, hypothesis testing, path analysis test, and Sobel test using SPSS version 26. The results of this study indicate that: (1) Dividend Policy has an effect on Debt Policy (2) Profitability has an effect on Debt Policy (3) Dividend Policy has an effect on Firm Value (4) Profitability has an effect on Firm Value (5) Debt Policy has an effect on Firm Value (6) Debt Policy is unable to mediate the relationship between Dividend Policy and Firm Value (7) Debt Policy is unable to mediate the relationship between Profitability and Firm Value.